Exploring Undergraduate Students' Translation Process Using Google Translate - Salem, Reham Derhim Hezam (University of Science and Technology, Sana'a, 2025)
This study aimed to explore the extent to which Yemeni undergraduate translation students engage in an effective translation process when translating Arabic texts into English using Google Translate (GT) and investigate factors affecting their translation. To achieve these objectives, a qualitative approach was employed. Three instruments were used to collect in-depth data: a checklist of Arabic sentences to be translated to English using GT and a think-aloud protocol employed during translation to explore the extent of students' engagement in the translation process using GT, and an interview conducted to gather data about factors that may affect their translation. Comparative analysis and thematic analysis methods were employed for analysing students' translation, compared to experts' translation, and for exploring factors affecting the translation process, respectively. Findings from comparative analysis revealed various deviation in most of the students' translations using GT compared to experts' translations. This deviation indicates students' limited engagement in the translation process, with minimal pre-editing and post-editing likely due to insufficient translation skills, vocabulary limitations, and challenges with cultural equivalents. Moreover, some students relied solely on GT without making any modification for GT output. The findings from the thematic analysis of interviews with students, in addition to think-aloud protocol, unveiled fostering and impeding factors that influence students' translation when using GT. Fostering factors included positive attitude toward MT, awareness of GT limitations, dissatisfaction with GT translations, think-aloud strategy, confidence in translating specific text types, understanding of translation technology strengths and limitations, awareness of cultural sensitivity, and attention to pre-editing and post-editing rules. On the contrary, impeding factors involved challenges faced by participants, lack of competence in using GT, negative effects of think-aloud, negative attitude toward GT, complexity of texts, difficulty in finding accurate equivalents, and incompetence in translation technology. The study provides theoretical and practical implications. Theoretically, it highlights the idea that the translation process using GT needs human expertise for effective translation. It also highlights factors affecting students' translation with GT which contribute to the understanding of translator competence in the digital age. Practically, the study informs educators of the importance of training on pre-editing the source text (ST) and post-editing GT outputs for effective use of GT. Further research can explore the use of other machine translation systems, including Artificial Intelligence (AI), in translating various text types.
Keywords: Google Translate; Translation process; Undergraduate students; Machine translation